A review of spectroscopy technology applications in transformer condition monitoring - Bakar, N.; Cui, H.; Abu-Siada, Ahmed; Li, S. (2016)
Spectroscopy is a powerful non-destructive technique that utilizes electromagnetic radiation interaction effect to determine the energy level and structure of atomic or molecular substance. In the last two decades, several researchers attempted to explore new various applications of spectroscopy technology in transformer condition monitoring. These applications include quantifying furan concentration in transformer oil samples which facilitate paper insulation aging assessment, estimating transformer oil interfacial tension number, and identifying contamination level in transformer oil. This paper presents a comprehensive review of the applications of the spectroscopy technology in power transformer condition monitoring and diagnostic. © 2016 IEEE.